Copper-based conductive block for pantograph of light rail vehicle and preparation method of copper-based conductive block

By adding materials such as rare earth high-entropy alloy powder and fine-grained iron powder in a specific proportion to the copper-based conductive block, and adopting powder metallurgy technology, the problems of large wear and poor stability of the copper-based conductive block are solved, significantly improving the wear resistance and arc resistance of the conductive block, and extending the service life.

CN119800146APending Publication Date: 2025-04-11HANGZHOU ADVANCE GEARBOX GRP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411737779.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing copper-based conductive blocks have a lot of wear in light rail vehicle pantograph applications, insufficient stability, short service life and high maintenance costs.

Method used

The ratio of copper powder, tin powder, lead powder, zinc powder, graphite powder, iron powder and composite multi-component rare earth high-entropy alloy powder is used to prepare conductive blocks through powder metallurgy processes, including cold pressing molding and high-pressure and high-temperature sintering, and optimize the microstructure of the material to improve conductive properties and wear resistance.

Benefits of technology

It achieves excellent wear resistance and self-lubricity of the conductive block, low resistivity, high strength and excellent arc ablation resistance, extending its service life to more than 20,000 kilometers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800146A_ABST
    Figure CN119800146A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-based conductive block for a pantograph of a light rail vehicle and a preparation method of the copper-based conductive block. The copper-based conductive block comprises the following materials in percentage by mass: 70-78% of copper powder; 5-8% of tin powder; 1-4% of lead powder; 2-5% of zinc powder; 0.5 to 1.5 percent of graphite powder; 8-15% of iron powder; and 0.5 to 2.0 percent of composite multi-component rare earth high-entropy alloy powder. According to the manufactured copper-based conductive block for the light rail vehicle pantograph, by adding the composite multi-component rare earth high-entropy alloy powder, the effects of stabilizing a molten pool and slowing down splashing of a Cu solution in an electric arc induced Cu molten pool can be achieved, so that excellent electric arc ablation resistance is obtained, the charged wear resistance of the material is improved, and the service life can reach more than 20,000 kilometers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-based conductive blocks, and in particular to a copper-based conductive block for a light rail vehicle pantograph and a preparation method thereof. Background Art

[0002] With the improvement of the national urbanization process, the scale of cities continues to expand. In order to meet the needs of urban transportation, a large number of urban rail transit have been built in various places in recent years. The conductive block used in the pantograph, as an important power-taking component of the electric locomotive, must have high thermal conductivity, sufficient mechanical strength, high tensile strength, good impact toughness, good wear resistance, low resistivity, high arc resistance and other comprehensive properties.

[0003] Copper-based powder metallurgy conductive block is one of the important parts in the pantograph of light rail vehicles. It uses its good conductivity and wear resistance to power the vehicle during movement. The characteristics of frequent replacement and high utilization rate require that the product material must have simple processing technology and low production cost. Therefore, copper-based powder metallurgy material will be a suitable choice. Powder metallurgy is a process technology that uses metal powder or a mixture of metal powder and non-metallic powder as raw materials, and then forms and sinters them to manufacture metal materials and metal composite materials. Copper-based powder metallurgy conductive blocks have been widely used due to their relatively low manufacturing cost, good applicability and quick and simple production process.

[0004] At present, copper-based conductive blocks are mainly used in pantographs of straddle-type monorail vehicles. The problems are that copper-based conductive blocks are prone to wear and tear and are not stable enough. The service life of existing conductive blocks in use in China is about 10,000 kilometers, which has a short service life and high maintenance costs.

[0005] The patent application with publication number CN109182833A discloses a copper-based powder metallurgy pantograph slide material with spherical chromium powder as a reinforcing phase and a preparation method thereof, wherein the chromium powder is spheroidized by a plasma spheroidizing device to obtain spherical chromium powder, which is mixed with other raw materials in a proportion, cold pressed and sintered to obtain the pantograph slide material. The cost of chromium powder spheroidization is high and the preparation process is relatively complicated.

[0006] The patent application with publication number CN112063880A discloses a copper-based powder metallurgy pantograph slide material for monorail vehicles and a preparation method thereof. It discloses a method for making a copper-based powder metallurgy conductive block. The components contained in the material and their mass percentages in the material are: copper powder 69-75%, graphite 5-7%, tin powder 4-6%, nickel powder 4-9%, chromium powder 1-3%, molybdenum disulfide 1-3%, and conductive ceramic 5-10%. The material resistivity is relatively large and the impact toughness is poor.

[0007] The patent application with publication number CN1932067A discloses a copper-based graphite and zirconium powder metallurgy composite material and its preparation method and use. The composite material is composed of the copper-based powder metallurgy material in the following alloy composition ratios (weight percentage): graphite 3.0-15.0%, chromium 1.0-2.0%, lead 4.0%, zinc 0-8.0%, tin 0-8.0%, zirconium 0.4-0.8%, and the balance is copper. The mixture of copper and zirconium powders adopts a specific production process to make an intermediate alloy powder. The entire process is complicated and the production cost is high. The impact strength of the material is 8.2-9J / cm 2 , the material's impact strength is low.

[0008] Patent CN105543534A discloses a copper-based pantograph slide material, which is based on copper powder and added with elements such as iron, chromium, nickel, zinc, tin, lead, and graphite. All elements are mixed and then cold pressed and sintered in a mesh belt furnace in an ammonia decomposition atmosphere. The material process is simple, but the friction coefficient is high and the wear is large. Summary of the invention

[0009] In order to solve the above technical problems, the purpose of the present invention is to provide a copper-based conductive block for a light rail vehicle pantograph and a preparation method thereof. The copper-based conductive block for a light rail vehicle pantograph prepared by the present invention has excellent wear resistance and self-lubrication, low resistivity, high strength and excellent resistance to arc erosion, and has a long service life.

[0010] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0011] A copper-based conductive block for a light rail vehicle pantograph, the constituent materials and their mass percentages are:

[0012] Copper powder 70-78%;

[0013] Tin powder 5-8%;

[0014] Lead powder 1-4%;

[0015] Zinc powder 2-5%;

[0016] Graphite powder 0.5-1.5%;

[0017] Iron powder 8-15%;

[0018] Composite multi-component rare earth high entropy alloy powder 0.5-2.0%.

[0019] Preferably, the copper powder has a particle size of -200 mesh electrolytic copper powder, a purity greater than 99.7%, and a dendritic morphology; the iron powder has a particle size of -300 mesh reduced iron powder, a purity greater than 98%, and an irregular shape; the tin powder has a particle size of -200 mesh, a purity greater than 99.0%; the zinc powder has a particle size of -200 mesh, a purity greater than 98.0%; the lead powder has a particle size of -200 mesh, a purity greater than 99.0%; the graphite powder is -200 mesh artificial graphite powder, and the carbon content is greater than 99%; the particle size of the composite multi-component rare earth high entropy alloy powder is -320 mesh.

[0020] Preferably, the composite multi-component rare earth high entropy alloy powder is rare earth-doped ZrMoCrNb high entropy alloy powder, wherein the proportion of ZrMoCrNb high entropy alloy powder is 99.8wt% and the proportion of rare earth is 0.2wt%; in the high entropy alloy powder, the molar ratio of each element is 1:1:1:1.

[0021] Preferably, in the rare earth doped ZrMoCrNb high entropy alloy powder, the rare earths are Ce and La.

[0022] Preferably, the weight ratio of Ce to La is 1:1.

[0023] A method for preparing the copper-based conductive block for a light rail vehicle pantograph as described above comprises the following steps:

[0024] (1) Ingredients: Weigh copper powder, tin powder, lead powder, zinc powder, graphite powder, iron powder and composite multi-component rare earth high entropy alloy powder according to the mass fraction of each component;

[0025] (2) Mixing: Put all the prepared raw materials into a V-type mixer and mix them evenly. The mixing time is 5-7 hours;

[0026] (3) Pressing: The uniformly mixed powder is weighed and re-placed into a cold pressing mold, and pressed on a four-column hydraulic press to obtain a pressed green sheet;

[0027] (4) Sintering: placing the green compact into a sintering mold and sintering it under pressure in a bell-type sintering furnace to obtain a copper-based conductive block blank for a pantograph;

[0028] (5) Processing: Machining the blank to product size.

[0029] Preferably, in step (3), the density of the compact is controlled at 6.4-6.6 g / cm 3 , pressing pressure 500-550MPa.

[0030] Preferably, in step (4), the sintering temperature is 800°C-840°C, the sintering pressure is 1.5-1.8 MPa, the holding time is 2.5-4 hours, and the blank density is controlled at 8-8.2 g / cm 3.

[0031] In the copper-based conductive block for the pantograph of a light rail vehicle of the present invention, iron powder is used as the hard phase of the material, and the iron powder is fine iron powder with a mesh size of -300 or more, so that the iron distribution in the conductive block matrix is ​​more uniform, the wear resistance of the material is effectively improved, and excellent conductive performance is provided; a small amount of -200 mesh artificial fine graphite is added to make the graphite distribution in the conductive block more uniform, and the conductive block has excellent friction reduction performance and self-lubricating performance; after adding 0.5-2.0% of the composite multi-component rare earth high entropy alloy powder, the electron dispersion caused by defects such as grain boundaries and dislocations in the copper matrix is ​​reduced. The alloy has a high strength and good electrical conductivity, and the alloy has a good electrical conductivity, and a good electrical conductivity. The alloy has a good electrical conductivity, and a good electrical conductivity. The alloy has a good electrical conductivity, and a good electrical conductivity. The alloy has a good electrical conductivity, and a good electrical conductivity. The alloy has a good electrical conductivity, and a good electrical conductivity. The alloy has a good electrical conductivity, and a good electrical conductivity. The alloy has a good electrical conductivity, and a good electrical conductivity. The alloy has a good electrical conductivity, and a good electrical conductivity.

[0032] The present invention places the pressed green sheet in a mold and then performs high-pressure and high-temperature sintering in a bell furnace to increase the density of the conductive block green sheet to 8-8.2 g / cm 3 Through this process, wear-resistant sintered blanks with controllable size, high density, low resistivity, good strength and stiffness can be obtained, which reduces the product processing allowance and reduces the product machining cost.

[0033] The present invention has the following beneficial effects due to the adoption of the above technical solution:

[0034] 1. The present invention uses a common powder press and a bell-shaped sintering furnace, which has low process cost, short production cycle and wide application prospects;

[0035] 2. The present invention adopts -300 mesh fine-grained iron powder to make the iron powder distribution more uniform, effectively improving the wear resistance and conductivity of the material; adopts -200 mesh fine-grained artificial graphite powder to make the graphite distribution in the material more uniform, so that the material has excellent friction reduction and self-lubricating properties, and improves the service life of the material;

[0036] 3. In the present invention, the addition of composite multi-component rare earth high entropy alloy powder can stabilize the molten pool and slow down the splashing of Cu solution in the arc-induced Cu molten pool, thereby obtaining excellent arc erosion resistance and improving the charged wear resistance of the material;

[0037] 4. The copper-based conductive block for the pantograph of a light rail vehicle manufactured by the present invention has excellent wear resistance and self-lubrication, low resistivity, high strength and excellent arc extinguishing performance, and its service life can reach more than 20,000 kilometers. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a picture of a copper-based conductive block for a light rail vehicle pantograph manufactured by the present invention. DETAILED DESCRIPTION

[0039] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0040] Embodiment 1:

[0041] The ingredients are prepared according to 75.5% copper powder, 7.5% tin powder, 2% lead powder, 3% zinc powder, 0.5% graphite powder, 11% iron powder and 0.5% composite multi-component rare earth high entropy alloy powder, wherein the composite multi-component rare earth high entropy alloy powder is Ce and La doped ZrMoCrNb high entropy alloy powder, the copper powder is -200 mesh copper powder, the iron powder is -300 mesh iron powder, the particle size of tin powder is -200 mesh, the particle size of zinc powder is -200 mesh, the particle size of lead powder is -200 mesh, and the graphite powder is -200 mesh graphite powder. All the prepared raw materials are mixed in a V-shaped mixer for 4 hours, and pressed into a copper-based conductive block blank on a 500-ton hydraulic press, and the density is controlled at 6.4-6.6 g / cm 3 The copper-based conductive block blank is placed in a special mold and hot isostatically pressed in a bell furnace at a sintering pressure of 15Kg / cm 2 , sintering temperature 820 ± 10 ℃, holding time 3 hours, to obtain the required copper-based conductive block sintered blank, the sintered blank is machined to achieve the following Figure 1 Final dimensions shown.

[0042] Embodiment 2:

[0043] The ingredients are prepared according to 75.5% copper powder, 7% tin powder, 2% lead powder, 3% zinc powder, 0.5% graphite powder, 11% iron powder and 1.0% composite multi-component rare earth high entropy alloy powder, wherein the composite multi-component rare earth high entropy alloy powder is Ce and La doped ZrMoCrNb high entropy alloy powder, the copper powder is -200 mesh copper powder, the iron powder is -300 mesh iron powder, the particle size of tin powder is -200 mesh, the particle size of zinc powder is -200 mesh, the particle size of lead powder is -200 mesh, and the graphite powder is -200 mesh graphite powder. All the prepared raw materials are mixed in a V-shaped mixer for 4 hours, and pressed into a copper-based conductive block blank on a 500-ton hydraulic press, and the density is controlled at 6.4-6.6 g / cm 3 The copper-based conductive block blank is placed in a special mold and hot isostatically pressed in a bell furnace. The sintered pressure blank is machined to achieve the following Figure 1 Final dimensions shown.

[0044] Embodiment 3:

[0045] The ingredients are prepared according to 75.5% copper powder, 6.5% tin powder, 2% lead powder, 3% zinc powder, 0.5% graphite powder, 11% iron powder and 1.5% composite multi-component rare earth high entropy alloy powder, wherein the composite multi-component rare earth high entropy alloy powder is Ce and La doped ZrMoCrNb high entropy alloy powder, the copper powder is -200 mesh copper powder, the iron powder is -300 mesh iron powder, the particle size of tin powder is -200 mesh, the particle size of zinc powder is -200 mesh, the particle size of lead powder is -200 mesh, and the graphite powder is -200 mesh graphite powder. All the prepared raw materials are mixed in a V-shaped mixer for 4 hours, and pressed into a copper-based conductive block blank on a 500-ton hydraulic press, and the density is controlled at 6.4-6.6 g / cm 3 The copper-based conductive block blank is placed in a special mold and sintered by hot isostatic pressing in a bell furnace at a sintering pressure of 18Kg / cm 2 , sintering temperature 820 ± 10 ℃, holding time 3 hours, to obtain the required copper-based conductive block sintered blank, the sintered blank is machined to achieve the following Figure 1 Final dimensions shown.

[0046] Embodiment 4:

[0047] The ingredients are prepared according to 75.5% copper powder, 6.5% tin powder, 2% lead powder, 3% zinc powder, 0.5% graphite powder, 10.5% iron powder and 2.0% composite multi-component rare earth high entropy alloy powder, wherein the composite multi-component rare earth high entropy alloy powder is Ce and La doped ZrMoCrNb high entropy alloy powder, the copper powder is -200 mesh copper powder, the iron powder is -300 mesh iron powder, the particle size of tin powder is -200 mesh, the particle size of zinc powder is -200 mesh, the particle size of lead powder is -200 mesh, and the graphite powder is -200 mesh graphite powder. All the prepared raw materials are mixed in a V-shaped mixer for 4 hours, and pressed into a copper-based conductive block blank on a 500-ton hydraulic press, and the density is controlled at 6.4-6.6 g / cm 3 The copper-based conductive block blank is placed in a special mold and sintered by hot isostatic pressing in a bell furnace at a sintering pressure of 18Kg / cm 2 , sintering temperature 820 ± 10 ℃, holding time 3 hours, to obtain the required copper-based conductive block sintered blank, the sintered blank is machined to achieve the following Figure 1 Final dimensions shown.

[0048] Comparative Example 1:

[0049] The ingredients are prepared according to 75.5% copper powder, 7% tin powder, 2% lead powder, 3% zinc powder, 0.5% graphite powder and 12% iron powder, wherein the copper powder is -200 mesh copper powder, the iron powder is -300 mesh iron powder, the particle size of the tin powder is -200 mesh, the particle size of the zinc powder is -200 mesh, the particle size of the lead powder is -200 mesh, and the graphite powder is -200 mesh graphite powder. All the prepared raw materials are mixed in a V-shaped mixer for 4 hours, and pressed into a copper-based conductive block blank on a 500-ton hydraulic press, and the density is controlled at 6.4-6.6g / cm 3 The copper-based conductive block blank is placed in a special mold and hot isostatically pressed in a bell furnace at a sintering pressure of 15Kg / cm 2 , sintering temperature is 820±10℃, holding time is 3 hours, the required copper-based conductive block sintered blank is obtained, and the sintered blank is machined to achieve the final shape size.

[0050] Comparative Example 2:

[0051] The ingredients are prepared according to 75.5% copper powder, 6.5% tin powder, 2% lead powder, 3% zinc powder, 0.5% graphite powder, 10% iron powder and 2.5% composite multi-component rare earth high entropy alloy powder, wherein the composite multi-component rare earth high entropy alloy powder is Ce and La doped ZrMoCrNb high entropy alloy powder, the copper powder is -200 mesh copper powder, the iron powder is -300 mesh iron powder, the particle size of tin powder is -200 mesh, the particle size of zinc powder is -200 mesh, the particle size of lead powder is -200 mesh, and the graphite powder is -200 mesh graphite powder. All the prepared raw materials are mixed in a V-shaped mixer for 4 hours, and pressed into a copper-based conductive block blank on a 500-ton hydraulic press, and the density is controlled at 6.4-6.6 g / cm 3 The copper-based conductive block blank is placed in a special mold and hot isostatically pressed in a bell furnace at a sintering pressure of 18Kg / cm 2 , sintering temperature 820±10℃, holding time 3 hours, obtain the required copper-based conductive block sintering blank, and machine the sintered blank. The copper-based conductive block produced according to this ratio and process is difficult to process in the subsequent machining process, and no processing test is performed.

[0052] Comparative Example 3:

[0053] The ingredients are prepared according to 75.5% copper powder, 7.0% tin powder, 2% lead powder, 3% zinc powder, 1.5% graphite powder and 11% iron powder, wherein the copper powder is -200 mesh copper powder, the iron powder and graphite powder are -100 mesh powder, the particle size of the tin powder is -200 mesh, the particle size of the zinc powder is -200 mesh, and the particle size of the lead powder is -200 mesh. All the prepared raw materials are mixed in a V-shaped mixer for 4 hours, and pressed into a copper-based conductive block blank on a 500-ton hydraulic press, and the density is controlled at 6.4-6.6g / cm 3The copper-based conductive block blank is placed in a special mold and hot isostatically pressed in a bell furnace at a sintering pressure of 18Kg / cm 2 , sintering temperature is 820±10℃, holding time is 3 hours, the required copper-based conductive block sintered blank is obtained, and the sintered blank is machined to achieve the final shape size.

[0054] The physical and mechanical properties of the copper-based conductive block samples prepared in Examples 1-4 and Comparative Examples 1 and 3 were tested according to the test method specified in the TB / T1842.1-2002 standard. The test results are shown in Table 1 below:

[0055] Table 1: Performance test results of copper-based conductive block samples prepared in Examples 1-4 and Comparative Examples 1 and 3

[0056]

[0057] It can be seen from the data in the above table: By comparing Examples 1-4 with Comparative Example 1, it can be seen that adding composite multi-component rare earth high entropy alloy powder can significantly reduce the charged wear of the material and greatly improve the service life of the material. Moreover, as the proportion of the added composite multi-component rare earth high entropy alloy powder increases, the hardness, impact toughness and tensile strength of the conductive block all show a slightly upward trend. However, according to Comparative Example 2, it can be seen that adding too much composite multi-component rare earth high entropy alloy powder in the conductive block will lead to difficulties in the subsequent machining of the conductive block. By comparing Comparative Example 1 and Comparative Example 3, it can be seen that the use of finer-sized graphite and iron powder can greatly improve the wear resistance of the material.

[0058] All features described in the description, the attached claims and the drawings are essential features for the invention both individually and in any combination.

[0059] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "an implementation", "specific implementation", "other implementations", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment, implementation or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described above may also be combined in a suitable manner in any one or more embodiments, implementations or examples. The technical solutions recorded in the present invention also include technical solutions formed by any one or more of the specific features, structures, materials or characteristics described above in a separate or combined manner.

[0060] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Ordinary technicians in the field can change, modify, replace, modify, delete some features, add features or re-combine features to form a technical solution in the above embodiments without departing from the principles and purpose of the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the innovative principles of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A copper-based conductive block for a light rail vehicle pantograph, characterized in that: The components and their mass percentages are: Copper powder 70-78%; Tin powder 5-8%; Lead powder 1-4%; Zinc powder 2-5%; Graphite powder 0.5-1.5%; Iron powder 8-15%; Composite multi-component rare earth high entropy alloy powder 0.5-2.0%.

2. The copper-based conductive block for a light rail vehicle pantograph according to claim 1, characterized in that: The copper powder has a particle size of -200 mesh electrolytic copper powder, a purity of more than 99.7%, and a dendritic morphology; the iron powder has a particle size of -300 mesh reduced iron powder, a purity of more than 98%, and an irregular shape; the tin powder has a particle size of -200 mesh, a purity of more than 99.0%; the zinc powder has a particle size of -200 mesh, a purity of more than 98.0%; the lead powder has a particle size of -200 mesh, a purity of more than 99.0%; the graphite powder is -200 mesh artificial graphite powder, and the carbon content is more than 99%; the composite multi-component rare earth high entropy alloy powder has a particle size of -320 mesh.

3. The copper-based conductive block for a light rail vehicle pantograph according to claim 1, characterized in that: The composite multi-component rare earth high entropy alloy powder is rare earth-doped ZrMoCrNb high entropy alloy powder, wherein the proportion of ZrMoCrNb high entropy alloy powder is 99.8wt%, and the proportion of rare earth is 0.2wt%; in the high entropy alloy powder, the molar ratio of each element is 1:1:1:

1.

4. A copper-based conductive block for a light rail vehicle pantograph according to claim 3, characterized in that: In the rare earth doped ZrMoCrNb high entropy alloy powder, the rare earths are Ce and La.

5. The copper-based conductive block for a light rail vehicle pantograph according to claim 4, characterized in that: The weight ratio of Ce to La is 1:

1.

6. A method for preparing a copper-based conductive block for a light rail vehicle pantograph as claimed in any one of claims 1 to 5, characterized in that: The steps include: (1) Ingredients: Weigh copper powder, tin powder, lead powder, zinc powder, graphite powder, iron powder and composite multi-component rare earth high entropy alloy powder according to the mass fraction of each component; (2) Mixing: Put all the prepared raw materials into a V-type mixer and mix them evenly. The mixing time is 5-7 hours; (3) Pressing: The uniformly mixed powder is weighed and re-placed into a cold pressing mold, and pressed on a four-column hydraulic press to obtain a pressed green sheet; (4) Sintering: placing the green compact into a sintering mold and sintering it under pressure in a bell-type sintering furnace to obtain a copper-based conductive block blank for a pantograph; (5) Processing: Machining the blank to product size.

7. The method for preparing a copper-based conductive block for a light rail vehicle pantograph according to claim 6, characterized in that: In step (3), the compact density is controlled at 6.4-6.6 g / cm 3 , pressing pressure 500-550MPa.

8. The method for preparing a copper-based conductive block for a light rail vehicle pantograph according to claim 6, characterized in that: In step (4), the sintering temperature is 800-840°C, the sintering pressure is 1.5-1.8 MPa, the holding time is 2.5-4 hours, and the blank density is controlled at 8-8.2 g / cm 3 .

Citation Information

Patent Citations

  • Copper-based pantograph sliding plate material and preparation method thereof

    CN105543534A

  • Copper-based powder metallurgical pantograph sliding plate material taking spherical chromium powder as strengthening phase and preparation method thereof

    CN109182833A

  • Copper-based powder metallurgy pantograph pan material for monorail vehicle and preparation method thereof

    CN112063880A

  • Copper-base graphite and sintered zirconium composite material and its prepn process and use

    CN1932067A